HAK DAN KEDUDUKAN CUCU SEBAGAI AHLI WARIS PENGGANTI DALAM SISTEM PEMBAGIAN WARIS DITINJAU DARI HUKUM WARIS ISLAM DAN KOMPILASI HUKUM ISLAM - HAZAR KUSMAYANTI; Lisa Krisnayanti (Universitas Islam Negeri Ar-Raniry, 2019)
Inheritance law is a part of civil law and is part of family law in particular. Inheritance law is closely related to human life, because every human being will experience a legal event, namely death. These legal events will cause legal consequences regarding the continuation of the rights and obligations of a person who has died and also in relation to his family or other people who have rights to their property. The purpose of this research is to know and understand the rights and position of grandchildren in the system of replacing the heirs in Islamic Inheritance Law and Compilation of Islamic Law and to know and understand the legal protection of grandchildren as heirs in the Islamic Inheritance Law and Compilation of Islamic Law. Based on the research, it can be concluded that the position of grandchild as a substitute heir in Islamic inheritance law is not listed in the Al-Quran and Hadith, only recognized through the Ijtihad conducted by the scholars. But in the Islamic Law Compilation the existence of grandchildren is recognized as a substitute for the parents who have died beforehand from the heirs and legal protection against grandchildren as successor heirs through the Compilation of Islamic Law which gives recognition of the position of substitute heirs through confirmation of the existence of heirs substitutes get full legalization where the provisions are not contained in the classic Islamic inheritance law. In addition, most Religious Judges in considering their decisions in terms of inheritance also see the arrangements contained in the Compilation of Islamic Law as a guide.